2018
DOI: 10.1172/jci.insight.123287
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional assessment of alveolar T cells in critically ill patients

Abstract: Pneumonia represents the leading infectious cause of death in the United States. Foxp3+ regulatory T cells promote recovery from severe pneumonia in mice, but T cell responses in patients with pneumonia remain incompletely characterized because of the limited ability to serially sample the distal airspaces and perform multidimensional molecular assessments on the small numbers of recovered cells. As T cell function is governed by their transcriptional and epigenetic landscape, we developed a method to safely p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 21 publications
2
84
0
Order By: Relevance
“…Measurement and analysis of DNA methylation was performed as previously described (McGrath-Morrow et al, 2018;Singer, 2019;Walter et al, 2018;Wang et al, 2018;Weinberg et al, 2019). Briefly, genomic DNA was isolated from sorted macrophage populations (Qiagen AllPrep Micro kit).…”
Section: Modified Reduced Representation Bisulfite Sequencingmentioning
confidence: 99%
“…Measurement and analysis of DNA methylation was performed as previously described (McGrath-Morrow et al, 2018;Singer, 2019;Walter et al, 2018;Wang et al, 2018;Weinberg et al, 2019). Briefly, genomic DNA was isolated from sorted macrophage populations (Qiagen AllPrep Micro kit).…”
Section: Modified Reduced Representation Bisulfite Sequencingmentioning
confidence: 99%
“…Modified reduced representation bisulfite sequencing. Genomic DNA was subjected to mRRBS as previously described (46,54,(59)(60)(61)(62). Bisulfite conversion efficiency averaged 99.52% ± 0.052% (SD) as estimated by the measured frequency of unmethylated CpGs in λ-bacteriophage DNA (New England BioLabs, #N3013S) added at a 1:200 mass ratio to each sample.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotype ontology (45) with the basal+extension association rule (constitutive 5 kb upstream and 1 kb downstream, up to 1000 kb max extension) against the whole genome as background. Metagene analysis was performed using SeqMonk's quantitation trend plot function across Treg cell-specific super-enhancer elements (19) after liftover of coordinates from the mm9 to the mm10 reference genome (59).…”
Section: Functional Enrichment Analysis Was Performed Using the Greatmentioning
confidence: 99%
See 1 more Smart Citation
“…Foxp3 dampen inflammatory responses to both endogenous and exogenous antigens. Aside from their role in maintaining immune homeostasis through their capacity to suppress over-exuberant immune system activation, Treg cells reside in healthy tissues and accumulate in the lung in response to viral injury to promote tissue repair (5,6). Our group and others have shown that in murine models of lung injury, Treg cells are master orchestrators of recovery (7)(8)(9)(10).…”
Section: Immunomodulatory Regulatory T (Treg) Cells Expressing the LImentioning
confidence: 99%